Elm Street School:A Case Study of Professional Development Expenditures - H. Alix Gallagher (Arizona State University, 2002)
This article addresses the question of how much is spent on teachers' professional development.  A review of the literature finds two problems that have frequently led to inaccurate estimates of professional development spending: 1) the accounting codes that are used in many studies provide little description of spending, and 2) studies generally focus on district or state expenditures for professional development, but do not collect data on school-level spending.  These problems are compounded by the fact that studies define professional development spending differently, and thus it is difficult to compare findings across studies.  In an effort to begin to address this problem, this study utilizes a detailed cost structure to analyze both district and school site expenditures on professional development across cost categories.  The study found that school-level expenditures were a significant source of professional development for teachers.  This has implications for the methodologies used to estimate current professional development expenditures and what level of expenditures would be necessary to generate dramatic improvements in student achievement.